Pengaruh Seragamisasi Celana/Rok Panjang dalam Mencegah Kejadian Demam Berdarah Dengue pada Siswa Sekolah Dasar - Mada Gautama Soebowo; Dias Irawan Prasetya; Soeharyo Hadisaputro; Sakundarno Adi (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2017)
DHF is still remains a health problem in Indonesia, especially in Semarang City. Based on data from Semarang City Health Office at 2014, DHF affected the age group 1-14 years as many sufferers of 1,065 (65%), in children ages 6-12 years old groups only has recorded 336 sufferers (ITP 20.6%). Several protective factors that prevent mosquito bite in children is wearing pants/skirt length, use of repellent, installation of bednet, and installation of net mosquitoes. The aims of this research was toprove whether wearing long pants/skirt could prevent the occurrence of DHF in elementary students. The design was a case control study. Total sample was 160 children (80 children per group) selected by proportional random sampling with due regard to inclusion and exclusion criteria. Data analysis was bivariate with chi-square test and multivariate logistic regression. There were variables that may prevented the incidence of DHF in school children which were wearing pants/long skirts at home (p=0.003; Or=2,781; 95% CI=1,412-5,476), installation of net mosquitoes in the windows (p=0,018; Or=2,462; 95% CI=1,166-5,200). Results of this research showed that the occurrence of DHF in children can prevented by wearing pants/long skirts at home, and the installation of net mosquitoes at windows home.